Interventional radiology management of high flow priapism: review of the literature - Arrichiello, Antonio; Angileri, Salvatore Alessio; Buccimazza, Giorgio; Di Bartolomeo, Francesco; Di Meglio, Letizia; Liguori, Alessandro; Gurgitano, Martina; Ierardi, Anna Maria; Papa, Maurizio; Paolucci, Aldo; Carrafiello, Gianpaolo (Acta Biomedica Atenei Parmensis, 2020)
INTRODUCTION:High-flow priapism is a persistent partial penile tumescence, related to high flow arterial blood into the corpora. In the treatment of high flow priapism, super-selective embolization is considered treatment of choice when conservative treatment fails as reported in the “EAU Guidelines on Priapism”, but there are only few series reporting the outcome, the efficacy of different embolic materials and these studies are uncontrolled and relatively small. OBJECTIVES:The aim of this study is to review the literature to outline the state of the art of this interventional treatment and to analyse the outcome of the different embolic agents. METHODS:Through Medline database we searched all the English-language published articles related to priapism. Keywords were chosen according to MeSH terms. We selected case-series from 1990 to 2020 including at least five cases of high-flow priapism.The variables extracted from the selected articles were: number of patients, mean age, diagnostic imaging modality, mono or bilateral involvement of the arteries, embolization material, technical success, clinical success, complications, recurrence rate and type of reintervention, mean follow up, onset of erectile dysfunction.RESULTS:We analyzed 11 papers.A total of 117 patients, mean age of 30 years, were studied during a period of 8 to 72 months. Technical success average was 99%, varying from 93 to 100%. Clinical success average was 88%, varying from 56 to 100%. After two or more treatments, resolution of priapism was obtained in all patients. No major adverse events registered. Recurrence rate of 21%(25/117) was observed, and only 4 pts underwent surgery. A total of 17 pts (15%) developed erectile dysfunction (ED).CONCLUSION: Our data suggested comparable outcomes using different types of materials.In line with the last evidences we suggest that the choice of the embolic material should be selected basing on the expertise of the operator, the characteristic of the fistula and characteristic of the patients.